Sertifikasi Kompetensi Bagi Perwira Kapal Penangkapan Ikan Pada Simulator Program Studi Teknologi Penangkapan Ikan Politeknik Negeri Pontianak - Rasidi Burhan; Ho Putra Setiawan; Slamet Jumaedi (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2021)
Abstrak This study aims to create a competency test device for simulator-based fishing vessel officers, the use of simulators is felt to be very effective and efficient in terms of various aspects. The location of the activity was carried out in 2 places, namely the Rengas River Beach Fishing Port and the Fishing Simulator Laboratory for the TPI Polnep Study Program. The method used in this study begins with identification by interview and questionnaire of each fishing gear totaling 10 people, the need and urgency of electronic navigation equipment in operating 3 types of fishing gear that exist in West Kalimantan, namely; 1) Bouke Ami fishing gear, 2) Purse Seine fishing gear and 3) Gillnet fishing gear. The second step is to analyze the questionnaire data which has a very important and important level of urgency with more than 5 respondents. Based on the results of data analysis, the type of electronic navigation equipment required for the operation of each fishing gear is obtained. In the competency test material for the operation of the Bouke Ami fishing gear there are 9 Competency Elements and 15 performance frameworks, while in the operation of the Purse Seine fishing gear there are 7 competency elements, with 13 performance frameworks, on the Gillnet tagkap tool there are 6 competency elements with 13 performance frameworks Key word: Fishing Simulator, Fishing Technology and MUK.